Simplify:  `root(8)(16x^12)^6` ` `

Expert Answers
justaguide eNotes educator| Certified Educator

The expression `(root(8) (16x^12))^6` has to be simplified.

`(root(8) (16x^12))^6`

= `(16x^12)^(6/8)`

= `16^(3/4)*(x^12)^(3/4)`

= `(2^4)^(3/4)*x^(12*(3/4))`

= `2^3*x^9`

= `8*x^9`

The expression `(root(8) (16x^12))^6 = 8*x^9`

oldnick | Student

`(root(8)(16x^12))^6=root(8)(2^24)root(8)(x^72)=2^3x^9=8x^9`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question